Transient Behavior Analysis for Solar Energy Storage in PCM-CFM Material Using Equivalent Heat Capacity Method as Storage Model - Murtadha, Talib K.; Salih, Hussien M M. S; Salman, Ali D. (Al-Khwarizmi Engineering Journal, 2019)
A paraffin wax and copper foam matrix were used as a thermal energy storage material in the double passes air solar chimney (SC) collector to get ventilation effect through daytime and after sunset. Air SC collector was installed in the south wall of an insulated test room and tested with different working angles (30o, 45o and 60o). Different SC types were used; single pass, double passes flat plate collector and double pass thermal energy storage box collector (TESB). A computational model based on the finite volume method for transient tw dimensional domains was carried out to describe the heat transfer and storage in the thermal energy storage material of collector. Also, equivalent specific heat method was employed to describe the heat storage and release in the mushy zone. Experimental results referred to an increase in thermal conductivity of paraffin wax that supported by copper foam matrix more than ten times. While the ventilation effect was still active for hours after the sun set, depending on the heat storage amount. Maximum ventilation mass flow rate with TESB collector was recorded with value equals to 36.651 kg/hr., when the overall discharge coefficient that was calculated for the system equals to 0.371. Experimental results showed that the best working angle range was 45~60o, and the highest air to the collector approaching temperature appeared to the double passes flat plate collector. Results gave greater heat storage efficiency of (47)% when the maximum solar radiation was 780 W/m2 at 12.00pm, while the energy summation through duration charge time was 18460 kJ. Computational results, depending on the equivalent heat capacity method for heat storage or release from phase change material that supported by copper foam matrix, showed the behavior of paraffin wax melting and solidification situation through periodic for charge and released heat from the solar collector. Also, these results gave agreement approaching the experimental results for the heat storage in the combined heat storage material, with standard error of 16.8%.